Microsoft SQL server 2005 reporting services - Misner, Stacia (Step by step (Redmond, Wash.), 2006)
Teach yourself the fundamentals of SQL Server Reporting Services-one step at a time. With this practical, learn-by-doing tutorial, you get the guidance you need to build flexible and powerful solutions that support the reporting needs of your organization. Discover how to: Install and configure Reporting Services Author, manage, and access reportsCreate attractive, information-rich reports with the Report DesignerCalculate values, organize information, and manipulate report dataBuild, deploy, and maintain a report modelRende.